(untitled) (Journal of Oriental Studies, 2023)
This article is dedicated to the research of Arabic-script historical and historical-biographical works of the 17th - the beginning of the 20th centuries and their information on the sacred geography of the Central Asian region. The article aims to identify and translate from the Chagatai and Persian languages and introduce new information about in the surroundings of Tashkent and Turkestan into academic discourse. The data of the Bukhara, Kokand, and Khiva manuscripts of the above period contain important and insufficiently studied data on sacred geography and the spiritual culture of the peoples of our region. In the process of working on written sources, based on historical and chronological analysis, the main range of Arabic-script works containing information on the sacred geography of the Central Asian region was identified. When studying these works Ansab al-salatin va tavarikh al-khavakin, Anjum at-tavarikh, Tarikh-i Jadida-yi Tashkand, biographical collections about representatives of the Muslim higher clergy, methods of Eastern source study were used. Based on the methods of critical selection and content analysis, the article examines the works of the authors of Arabic-script manuscripts, which contain original information about sacred places located in the vicinity of Tashkent and Turkestan. For the first time, extracts from historical and historical-biographical works of the 17th - the beginning of the 20th centuries are introduced into academic discourse, which complements general information on the history of the spiritual culture of the peoples of our region. This article was prepared as part of a scientific project funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan, (Grant No. AP АР09259919). Keywords: Arabic-script manuscripts, historical geography, sacred places, Tashkent vilayat, Turkestan